The Limits and Possibilities of “Garage”: An Ethnographic Exploration on the Local Transportation System of Bahong, La Trinidad, Benguet amid the COVID-19 Pandemic - Dela Torre, Jessel G.; Guerrero, Sophia Jireh D.; Guazon, Hector (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology; Vol 1 No 2 (2023): The Flow of Things and Bodies: The Production of Flowers in La Trinidad, Benguet, 2025)
The study investigates the emergence of the informal transport system in Bahong, the driver’s aspirations, the challenges this entails to the community, and the significant role it plays to the mobility of the residents, especially amid the conditions of COVID-19.